Sakralna baština župe Staševica - Jukić, Ivan; Prlić, Vinko (Split : Zbornik Kačić ; Staševica : Župski ured sv. Staša, 2011)
Summary
Zusammenfassung
Bibliografija: str. 108
Kazala
Keywords: župe; crkve; franjevci; sakralna umjetnost